Manipulating and probing the growth of plasmonic nanoparticle arrays using light - BULFIN, BRENDAN; FLEISCHER, KARSTEN; USOV, VICTOR; MCGILP, JOHN; SHVETS, IGOR (My University, 2013)
Highly ordered self-assembled silver nanoparticle (NP) arrays have been produced by glancing angle deposition on faceted c-plane Al2O3 templates. The NP shape can be tuned by changing the substrate temperature during deposition. Reflectance anisotropy spectroscopy has been used to monitor the plasmonic evolution of the sample during the growth. The structures showed a strong dichroic response related to NP anisotropy and dipolar coupling. Furthermore, multipolar resonances due to sharp edge effects between NP and substrate were observed. Analytical and numerical methods have been used to explain the results and extract semi-quantitative information on the morphology of the NPs. The results provide insight on the growth mechanisms by the glancing angle deposition. Finally, it has been shown that the NP morphology can be manipulated by a simple illumination the surface with an intense light source, inducing changes in the optical response. This opens up new possibilities for engineering plasmonic structure over large active areas.
PUBLISHED
Keywords: reflectance anisotropy spectroscopy; plasmonic; nanoparticle array; quadrupolar; Nanoscience & Materials